Efficient generation of genetically distinct pigs in a single pregnancy using multiplexed single‐guide RNA and carbohydrate selection. (2nd September 2014) - Li, Ping; Estrada, Jose L.; Burlak, Christopher; Montgomery, Jessica; Butler, James R.; Santos, Rafael M.; Wang, Zheng‐Yu; Paris, Leela L.; Blankenship, Ross L.; Downey, Susan M.; Tector, Matthew; Tector, A. Joseph
Abstract Background Manipulating the pig genome to increase compatibility with human biology may facilitate the clinical application of xenotransplantation. Genetic modifications to pig cells have been made by sequential recombination in fetal fibroblasts and liver‐derived cells followed by cross‐breeding or somatic cell nuclear transfer. The generation of pigs for research or organ donation by these methods is slow, expensive and requires technical expertise. A novel system incorporating the bacterial nuclease Cas9 and single‐guide RNA targeting a 20 nucleotide site within a gene can be expressed from a single plasmid leading to a double‐strand break and gene disruption. Coexpression of multiple unique single‐guide RNA can modify several genetic loci in a single step. We describe a process for increasing the efficiency of selecting cells with multiple genetic modifications. Methods We used the CRISPR/Cas system to target the GGTA1, CMAH and putative iGb3S genes in pigs that have been naturally deleted in humans. Cells lacking galactose α‐1, 3 galactose (α‐Gal) were negatively selected by an IB4 lectin/magnetic bead. α‐Gal negative multiplexed single‐guide RNA‐treated cells were used for somatic cell nuclear transfer (SCNT) and transferred to fertile sows. We examined the levels of α‐Gal and Neu5Gc expression of 32 day fetuses and piglets and analyzed the targeted genes by DNA sequencing. Results Liver‐derived cells treated with multiple single‐guide RNA and selected for an α‐Gal null phenotype were significantly more likely to also carry mutations in simultaneously targeted genes. Multiplex single‐guide RNA‐treated cells used directly for SCNT without further genetic selection produced piglets with deletions in the targeted genes but also created double‐ and triple‐gene KO variations. CRISPR/Cas‐treated cells grew normally and yielded normal liters of healthy piglets via somatic cell nuclear transfer. Conclusions The CRISPR/Cas system allows targeting of multiple genes in a single reaction with the potential to create pigs of one genetic strain or multiple genetic modifications in a single pregnancy. The application of this phenotypic selection strategy with multiplexed sgRNA and the Cas9 nuclease has accelerated our ability to produce and evaluate pigs important to xenotransplantation.